2022
DOI: 10.1177/09612033221101731
|View full text |Cite
|
Sign up to set email alerts
|

Association between interferon-I producing plasmacytoid dendritic cells and thrombotic antiphospholipid syndrome

Abstract: Background: Thrombotic risk in antiphospholipid syndrome (APS) is conferred by the association of antiphospholipid (aPL) antibodies (first hit) with additional pro-coagulant stimulus (second hit), such as inflammation. Among inflammatory responses, the production of large amounts of interferon (IFN)-I by plasmacytoid dendritic cells (pDCs) is at the basis of the pathophysiology of systemic autoimmune disorders, which raises the hypothesis that this mechanism could also be associated with vascular manifestation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…PAPS and SAPS share the expression of genes involved in the type 1 interferon signature, inflammation and atherosclerosis ( 10 ), whereas PAPS differs from systemic lupus erythematosus (SLE) by the expression of genes related to mitochondrial function, oxidative stress and antioxidant capacity ( 10 , 18 , 19 ). We recently observed that genes related to the type 1 interferon signature were overexpressed in t-SAPS, but not in t-PAPS, compared to controls ( 20 ), suggesting that the inflammatory profile is different between these two presentations of APS. A recent meta-analysis identified 16 genes differentially expressed in t-PAPS compared to controls that were expressed in 32 different tissues, which may explain the fact that thrombosis in APS occurs in any vascular site ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…PAPS and SAPS share the expression of genes involved in the type 1 interferon signature, inflammation and atherosclerosis ( 10 ), whereas PAPS differs from systemic lupus erythematosus (SLE) by the expression of genes related to mitochondrial function, oxidative stress and antioxidant capacity ( 10 , 18 , 19 ). We recently observed that genes related to the type 1 interferon signature were overexpressed in t-SAPS, but not in t-PAPS, compared to controls ( 20 ), suggesting that the inflammatory profile is different between these two presentations of APS. A recent meta-analysis identified 16 genes differentially expressed in t-PAPS compared to controls that were expressed in 32 different tissues, which may explain the fact that thrombosis in APS occurs in any vascular site ( 18 ).…”
Section: Discussionmentioning
confidence: 99%